A Study on Emerging Hr Trends in the Year 2022 with Special Reference to Artificial Intelligence - A.Manojkumar; N.Bharath Yuvaraj (East Asian Journal of Multidisciplinary Research, 2022)
COVID-19 pandemic is a crisis that is testing both the professional and personal relations of the world. It has also affected the HR tech industry, and has challenged the organizations which were not technologically advanced to rethink over the working and activities according to the conditions. The research paper is descriptive in nature. The researcher was used secondary data where the data was collected from research papers, publications, websites, HR blogs, survey reports etc. The core objective of the study was examine the recent HR trends post covid-19 as well as the role of artificial intelligence in human resource department and understand the challenges in HR department. The study has taken into account the HR trends followed in the company Deloitte. The research study has concluded that a role of AI is larger into various functions carried out in human resource department where by robotics companies can handle recruitment, hiring, analysing the data, colleting the data, reducing workload at workplace and enriching workplace efficiency.